PERBANDINGAN UJI EFEKTIVITAS EKSTRAK BENGKUANG (PACHYRIZUS AROSUS) DAN DAUN SIRIH HIJAU (PIPER BETLE L.) TERHADAP BAKTERI PROPIONIBACTERIUM ACNES - I Nyoman Ehrich Lister (Jurnal Keperawatan Priority, 2021)
Propionibacterium acnes is a gram-positive bacteria and consists of the Propionibacteriaceae family. Propionibacterium acnes is a bacteria that causes acne or acne vulgaris, a disease that is quite disturbing and gets the attention that occurs in adolescents and young adults. This research aimed to compare and determine the effectiveness of the extract of yam (Pachyrizus arosus) and green betel leaf (Piper betle L.) in inhibiting the growth of Propionibacterium acnes bacteria. The research variables were concentrations of yam extract (Pachyrizus arosus) 5%, 10%, 15%, 20% and green betel leaf (Piper betle L.) 1,5%, 3%, 5%, 7,5%. The results showed that there was an inhibiting zone against the growth of Propionibacterium acnes bacteria.